Principal Functions of Non-Selfadjoint Sturm-Liouville Problems with Eigenvalue-Dependent Boundary Conditions - Nihal Yokuş (Abstract and Applied Analysis)
We consider the operator 𝐿 generated in 𝐿2(ℝ+) by the differential expression 𝑙(𝑦)=−𝑦+𝑞(𝑥)𝑦, 𝑥∈ℝ+∶=[0,∞) and the boundary condition 𝑦(0)/𝑦(0)=𝛼0+𝛼1𝜆+𝛼2𝜆2, where 𝑞 is a complex-valued function and 𝛼𝑖∈ℂ, 𝑖=0,1,2 with 𝛼2≠0. In this paper we obtain the properties of the principal functions corresponding to the spectral singularities of 𝐿.